Evoking the muses: Exploring the nature of inspiration in art museums - Shields, Emily (My University, 2025)
Art museums have a unique capacity to elicit positive emotions, with inspiration emerging as a particularly meaningful yet underexplored emotion. This quantitative study investigated whether and how adults experience inspiration during art museum visits. Data were collected through semi-structured interviews with 54 adults at three U.S. art museums. Results indicate that inspiration is a common emotional response during art museum visits, often characterized by shifts in perspective, feelings of motivation, and admiration. Participants attributed their inspiration to various aspects of the art museum experience, including personal relevance, the formal qualities of artworks, the perceived intent of artists, and the juxtaposition of different artistic ideas. While inspiration was strongly reported, participants also experienced related emotions such as joy and excitement. Findings support the belief that inspiration correlates with perspective shifts and motivation. The study contributes to the growing body of research highlighting the emotional impacts of museum visits and underscores the potential of inspiration to support visitor well-being. Implications for museum practice include enhancing interpretative strategies to foster personal meaning-making and promoting continued engagement beyond the museum visit. Further research is recommended to explore the long-term impacts of museum-inspired motivation and to diversify participant demographics.
Thesis (Master's)--University of Washington, 2025